2016
DOI: 10.5755/j01.ct.67.1.15003
|View full text |Cite
|
Sign up to set email alerts
|

Application of waste materials as potential biosorbents for Cu(II) and Zn(II) removal

Abstract: Mining is probably the most common activity that fundamentally impacts the country. The problems connected with the extraction of sulphide ores arise especially during the final stage of mining, closure and abandonment of the extraction area, when the conditions for the generation of strong acid water are most likely to occur. With respect to the diversity of compounds in acid mine drainage (AMD) and its low pH values it is hard to find an effective and inexpensive "active" treatment process. Recently, numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…The study of changes adsorption capacity at equilibrium conditions are shown in Tables 5 and 6. These results correspond with previous study [30] that deals with adsorption of Cu(II) and Zn(II) by raw poplar sawdust. It was revealed that the poplar sawdust better correlated to the Langmuir´s model.…”
Section: Adsorption Studysupporting
confidence: 93%
See 2 more Smart Citations
“…The study of changes adsorption capacity at equilibrium conditions are shown in Tables 5 and 6. These results correspond with previous study [30] that deals with adsorption of Cu(II) and Zn(II) by raw poplar sawdust. It was revealed that the poplar sawdust better correlated to the Langmuir´s model.…”
Section: Adsorption Studysupporting
confidence: 93%
“…The natural poplar wooden sawdust exhibited a metal ion removal efficiency of approximately 80%. These results correspond with the study Holub et al [30] dealing with adsorption of Cu(II) and Zn(II) from single-component aqueous solutions onto non-modified poplar sawdust (concentrations range from 1 to 150 mg.L -1 ). The authors [9,10,30] also report that low-cost waste materials like wooden sawdust could be used as economically viable for the removal of heavy metal ions in acidic conditions.…”
Section: Adsorption Studysupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, industrial hemp is used to treat water. It is a component of adsorbents which bond and remove metal ions and bisorbents which capture copper and zinc ions [18][19][20]. Enriched bio-char substrates from hemp pre-treated with hematite, melanterite, and dolomite and subjected to pyrolysis at 400°С have been shown to reduce the concentration of phosphorous in water from 15.5 mg/l to less than 2 mg/l, thereby preventing the epitrophy of water bodies [21].…”
Section: Current State Of Affairs and Analysis Of Prospects Of Applic...mentioning
confidence: 99%
“…In last two decades is booming for the use of low cost organic materials for heavy metal ions removal. It started with the application of biomass and agricultural waste materials as peat, rice husk, leaves or seeds (Bailey et al 1999;Vieira and (Bailey et al 1999;Demcak et al 2017b) Sawdust 3.9 3.7 -7.3 - (Bailey et al 1999;Holub et al 2016) Volesky 2000; Demcak et al 2017a). The major advantages of adsorption on natural sorbents in comparison to conventional methods include low cost, high efficiency, minimization of chemical or biological sludge, no additional nutrient requirement, regeneration of biosorbents, and possibility of metal recovery (Leng et al 2015).…”
Section: Introductionmentioning
confidence: 99%